A New Dominant Gene for Resistance to Whitebacked Planthopper in Rice - Fa Wu, Chun; Khush, Gurdev S. (Wiley, 1985)
The mode of inheritance and allelic relationships of genes for resistance to whitebacked planthopper, Sogatella furcifera (Hbrvath), in 15 resistant cultivars of rice, Oryza sativa L., were studied. One‐leaf stage seedlings were artificially infested with second‐ and third‐instar whitebacked planthopper nymphs. Reactions of the seedlings were recorded when the susceptible check, ‘Taichung Native 1’, (TN1) was completely killed. The reactions of F1, F2, and F3 progenies from the crosses of test cultivars with TN1 revealed that single dominant genes confer resistance in ‘Boegi Boera’, ‘DD4’, PI 184675‐6, ‘Siam Garden’, ‘Rening’, ‘N'Diang Marie’, ‘Manggar’, ‘Oha’, ‘Gokhue Saier’, ‘Tjempo Tolo’, and ‘Nemai‘. Two independent dominant genes govern resistance in ‘ARC5752’, ‘Chaia Anaser’, ‘Katuyhar Dhan’, and ‘Dhera Dun Basmati’. Tests for allelism revealed that the single dominant genes in Boegi Boera, DD4, PI 184675‐6, Siam Garden, Rening, Oha, Gokhue Saier, Tjempo Tolo, and Nemai, and one of the two independent dominant genes in ARC5752, Chaia Anaser, Katuyhar Dhan, and Dhera Dun Basmati are allelic to Wbph 1, and that the second gene in ARC5752 is allelic to Wbph 2. The second gene in Chaia Anaser, Katuyhar Dhan, and Dhera Dun Basmati was allelic to Wbph 3. The single dominant genes of N'Diang Marie and Manggar segregated independently of Wbph 1, Wbph 2, and Wbph 3. The dominant gene of N'Diang Marie was designated an Wbph 5. The allelic relationships of the dominant gene from Manggar to Wbph 5 are not known.